(3GdJMbjb aj GdbQGAI HGdLje GdTOjOI hUaGJgG heNQLgG def jQjOgs - (3eMeO Hf eMeO GdYjOs ((3eMeO GdCejf Hf eMeO HhHG s)
(3ChdgG (B:s
(3CSjQ PfHg GdeQJLi Yah QHg GdTjN eMeO Hf eMeO GdYjO HSe Gddg hHg CKb hYdjg CJhcd f hHYO aEf GdLje GdNGdUI gi GdefYbOI , hJhUa HGdLgQ hGdTOI s
(3BNQgG (B:s
(3bGd HYVge (B: (3JMbjbGfG eNGQL GdMQha , JdGhI GdbQBf def Jcda Hg Shi eG ai GdcdGe YGOI de Jce GdLje HgG ePchQI s
(3HBNQgG JbQjX deMeO Hf eMeO GdeUWai Hf eMeOs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeYgO GdehQjJGfi ddHMK GdYdei (B((3dZI YQHjI (B: (3CUhGJ (B1742) s
Keywords: (3GddZIs